2019
DOI: 10.1038/s41534-019-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Biphoton shaping with cascaded entangled-photon sources

Abstract: Quantum entanglement is an integral part of quantum optics and has been exploited in areas such as computation, cryptography and metrology. The entanglement between photons can be present in various degrees of freedom (DOFs), and even the simplest bi-partite systems can occupy a large Hilbert space. Therefore, it is desirable to exploit this multi-dimensional space for various quantum applications by fully controlling the properties of the entangled photons in multiple DOFs. While current entangled-photon sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…As one can see, the interference pattern contains additional contributions originating from interferometers with different gaps. The ability to manipulate the interference patterns opens up possibilities for quantum state engineering 20,35 .…”
Section: Proof-of-concept Gas Sensing Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one can see, the interference pattern contains additional contributions originating from interferometers with different gaps. The ability to manipulate the interference patterns opens up possibilities for quantum state engineering 20,35 .…”
Section: Proof-of-concept Gas Sensing Experimentsmentioning
confidence: 99%
“…Nonlinear interferometers have been realized using numerous physical platforms, including bulk nonlinear crystals [11][12][13][14][16][17][18] , gas cells 19 , fiberized networks 20,21 , and nonlinear waveguides 22,23 . Additionally, nonlinear interferometers have been used for imaging 24 , spectroscopy 16,[25][26][27] , optical coherence tomography 28,29 , superresolution interferometry 18,19 , and polarimetry 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigations into nonlinear interferometers, a subset of which are commonly labelled as SU(1,1) interferometers [18,19], have shown that these systems can be also used to characterize coherence properties of the quantum light involved and may even offer practical quantum advantages [20][21][22]. Recent experiments employing this class of interferometers have shown compelling results for both fundamental and applied physics, such as the recent demonstrations of wide-field interferometry and bi-photon shaping [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…|H /|V denotes the horizontally/vertically polarized polarized photon states and |ω s/i,n denotes the state of signal/idler photon with center frequency ω s/i,n which satisfies ω s,n +ω i,n =const [19][20][21][22]. The generation of this state has been studied in many schemes, such as a two-period quasi-phase-matching nonlinear waveguide scheme [22] and a cascaded photon pair source [23]. Notations of discretized frequency-bins are used in Eqn.(1) for the ease of discussion, but the results of this letter can also be applied to continuous frequency entanglement.…”
mentioning
confidence: 99%